Present Status of Epidemiology, Risk Factors and Screening of Pancreatic Cancer in China - YANG Huan (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Pancreatic cancer (PC) is one of most fatal cancers worldwide. According to the 2020 cancer registry data, PC was the 12th common cancer and the 7th leading cause of cancer deaths globally. PC is a rare cancer, but the 5-year survival is very low because of its rapid progress and poor prognosis. The disease burden of PC in China is quite different from western countries, indicating that the distribution of genetic factors, lifestyle and environmental factors varies from different regions. This article reviews the epidemiology, etiology and screening of PC in China, to provide systematic references for PC prevention and control.